The Impact of Social Media on the Mental Health of Teenagers - Chizoba Grace Ezekperechi (dialektika kontemporer, 2024)
Adolescents are increasingly unable to envision their lives without social media, necessitating that healthcare providers assess its risks as a new factor in their well-being. While concrete empirical data is scarce, both teen and professional viewpoints significantly shape the perceived relationship between social media and mental health. The risks tied to adolescents’ social media engagement include privacy issues, cyberbullying, negative impacts on academic performance, and mental health challenges. Nonetheless, responsible use of social media can enhance social connections and dialogue, boost self-esteem, promote wellness, and provide access to essential health information. Despite growing concerns about social media’s adverse effects on young people’s mental health, research into how adolescents perceive and interact with social media, especially as a source of knowledge or a means for self-expression within broader media narratives, remains limited. The widespread use of cell phones and other media by young people contributes to chronic sleep deprivation, adversely affecting cognitive functions, academic achievement, and socio-emotional development. Various studies, including cross-sectional, longitudinal, and empirical research, have linked teen smartphone and social media use to increased mental distress, self-harm, and suicidal behaviors. By employing open, nonjudgmental, and age-appropriate strategies, including educational interventions and practical problem-solving, clinicians can help youths and their families mitigate the risks associated with social media and smartphone use.